Effects of Fermentation Temperature on Key Aroma Compounds and Sensory Properties of Apple Wine. Issue 12 (28th October 2015) - Peng, Bangzhu; Li, Fuling; Cui, Lu; Guo, Yaodong
Abstract: Fermentation temperature strongly affects yeast metabolism during apple wine making and thus aromatic and quality profiles. In this study, the temperature effect during apple wine making on both the key aroma compounds and sensory properties of apple wine were investigated. The concentration of nine key aroma compounds (ethyl acetate, isobutyl acetate, isopentylacetate, ethyl caprylate, ethyl 4‐hydroxybutanoate, isobutylalcohol, isopentylalcohol, 3‐methylthio‐1‐propanol, and benzeneethanol) in apple wine significantly increased with the increase of fermentation temperature from 17 to 20 °C, and then eight out of the nine key aroma compounds with an exception of ethyl 4‐hydroxybutanoate, decreased when the temperature goes up 20 to 26 °C. Sensory analysis showed that the apple wine fermented at 20 °C had the highest acceptance for consumers. Fermentation at the temperature of 20 °C was therefore considered to be the most suitable condition using the selected yeast strain ( Saccharomyces cerevisiae AP05) for apple wine making. Changes in the fermentation temperature can considerably affect the production of key aroma compounds and sensory profiles of apple wine. These results could help apple wine producers make better quality production for consumers at the optimal fermentation temperature.